O podstawowych stanowiskach w etyce antycznej - Husserl, Edmund (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2016)
Translated text comes from Edmund Husserl’s course “Einleitung in die Ethik” [“Introduction into Ethics”] from the spring semester 1920, repeated and extended in the spring semester 1924, each time in Freiburg. Husserl presents Socrates as a reformer of philosophy and philosophical practice – in his criticism of sophistic, skepsis and empiricism. As Bogaczyk-Vormayr emphasizes in her introduction, Husserl does not evoke any historical paradigm, he does not want to – simply said – be a historian of philosophy; on the contrary, he presents his view of ethics, which we should call a phenomenological one. That means he offers a critical history of philosophy – his analyses are focused on philosophical ideas and only their philosophical potential is what matters to him.
Keywords: Socrates; Socratic dialogue; praxis; sophistic; truth; phenomenology; eudaimonia; happiness; wisdom